Antibiotic Consumption and Bacterial Resistance Rates in Hospitalized COVID-19 Patients: A Retrospective Study During the 3 First Surges. (16th December 2022) - Jaffal, Karim; Bouchand, Frédérique; Lawrence, Christine; Mascitti, Hélène; Duran, Clara; Annane, Djillali; Dinh, Aurélien
Abstract : In our hospital, during COVID-19 pandemic, overall consumption of antibiotics increased during the three first surges, mainly due to ICU prescription However, antibiotic consumption decreased in the Infectious Diseases Department. Rates of ESBL Enterobacterales remained stable.